REVERSE LOGISTICS IN CONNECTION WITH WASTE MANAGEMENT (Perner's Contacts, 2010)
This article focuses on waste management and its connection with reverse logistics, case study of waste management in the Pardubice public transport company. Article focuses on suggesting an alternative way of waste processing of polluted diluents. Improving waste processing could gain expenses saving and generate more profit from this area.